1975
DOI: 10.1542/peds.55.2.224
|View full text |Cite
|
Sign up to set email alerts
|

Transcutaneous Determination of Arterial Oxygen Tension

Abstract: Arterial oxygen tension measurements were performed simultaneously using two different techniques: (1) the conventional method of analyzing a blood sample obtained from the radial artery by means of a Clark electrode and (2) a new method of transcutaneous oxygen tension recording using a newly developed surface electrode containing a built-in heating device to ensure optimal cutaneous perfusion at the site of measurement. Two groups of newborn infants were used as subjects: (1) 70 clinically hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1976
1976
2002
2002

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Fenner et al [2] found that the partial pressure of transcutaneous oxygen (P tc O 2 ) is directly proportional to PaO 2 . Correlation and proper calibration ought to be performed in order to relate the transcutaneous measurements to their corresponding arterial equivalents.…”
Section: Introductionmentioning
confidence: 99%
“…Fenner et al [2] found that the partial pressure of transcutaneous oxygen (P tc O 2 ) is directly proportional to PaO 2 . Correlation and proper calibration ought to be performed in order to relate the transcutaneous measurements to their corresponding arterial equivalents.…”
Section: Introductionmentioning
confidence: 99%